Characteristics of Mineral Contents and Elements Composing Basalt Rock for Hot Stone Massage - Arisa, Ma’rifani Fitri; Novita, Elok; Agrevinna, Mausa (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2024)
This research seeks to accomplish two objectives: first, to identify the mineral makeup and elements that comprise basalt rock used for hot stone massage, and second, to determine the physical characteristics of the basalt rock employed for this purpose. Currently, basalt rock is not utilized in Indonesia for hot stone massage, and the mineral content and elements that make up this rock remain unknown. Consequently, it is crucial to determine the mineral makeup and physical characteristics of basalt rock used for hot-stone massage. This study employed experimental laboratory research methods using an observation technique to gather data. The samples were analyzed using an experimental approach at the Quality Control Laboratory, using XRD and XRF instruments to determine the mineral content and elements that make up basalt rock for hot stone massage. The results of this research reveal that the mineral contents and elements that make up basalt rock for hot stone massage include oxide compounds, such as SiO2, Al2O3, Fe2O3, K2O, MgO, and Na2O. Additionally, the physical characteristics of basalt rock, including its dark color, fine-grained texture, and igneous origin, make it suitable for use in hot-stone massage. Furthermore, basalt rock is advantageous to human health.